Kontribusi Usahatani Bayam Terhadap Pengeluaran Rumah Tangga Petani: Sebuah Analisis Ekonomi - Midiansyah Effendi; Herwan Galingging; Gisky Andria Putra (JSEP (Journal of Social and Agricultural Economics), 2023)
Every farmer hopes to earn a decent income, including spinach farmers. Given the high demand for spinach in Berau Regency, this study aimed to determine the income from spinach farming in Karang Ambun Village, Tanjung Redeb District, Berau Regency. This research was a descriptive study with a quantitative approach. The number of samples was 40 respondents and the sampling technique was carried out using the purposive sampling technique and data analysis using the method of farming income analysis and percentage calculating the contribution of farm income to farm household expenditure. The results of the analysis show that the income earned by farmers in Karang Ambun Village, Tanjung Redeb District, Berau Regency was IDR 17,635,056 per planting period, and the average income was IDR 440,876 per person. The feasibility analysis of the level obtained a number of 1.60, which means that spinach farming can be said to be profitable and feasible to cultivate. The calculation of the income to expenditure ratio of farmer households was 30.63%, which means that approximately 1/3 of the average expenditure per capita of farmer households can be covered by spinach farming.